Assessment of the efficacy of tuina on treating cervicogenic headache: A protocol for systematic review and meta-analysis. Issue 22 (4th June 2021) - Qian, Xin; Ma, Dongyang; Liu, Jiayi; Pan, Ting; Wang, Haili; Hu, Zhe; Wang, Zhaohui; Qi, Wei
Abstract: Background: Cervicogenic headache is a secondary headache characterized by unilateral headache, symptoms, and signs of neck involvement. It is often worsened by neck movement, sustained awkward head position, or external pressure over the upper cervical or occipital region on the symptomatic side. In this systematic review, we aimed to evaluate the efficacy and safety of massage therapy for the treatment of cervicogenic headache. Methods: We searched the China National Knowledge Infrastructure, Chinese Scientific Journal Database, Wanfang Database, China Doctoral Dissertations Full-Text Database, China Master's Theses Full-Text Database, Cochrane Central Register of Controlled Trials, PubMed, and Embase. We will select all eligible studies published on or before April 1, 2021. We will use Review Manager 5.4, provided by the Cochrane Collaborative Network for statistical analysis. We then assessed the quality and risk of the included studies and observed the outcome measures. Results: This meta-analysis further confirmed the benefits of tuina in the treatment of cervicogenic headache. Conclusion: The purpose of this meta-analysis was to explore the effect of tuina on patients with cervicogenic headache and to provide more options for clinicians and patients to treat cervicogenic headache. Ethics and dissemination: This systematic review will evaluate the efficacy and safety of tuina in the treatment of cervicogenic headache. Since all the data included were published, the systematic review did not require ethical approval. Registration number: INPLASY202150053.